Analysis Of Factors Affecting Employee Job Satisfaction At Bank Syariah Indonesia In Ternate - A Kamis, Ruslan; Husen, Zulaiha; Ridwan, Ika Wulandari (Jurnal Ilmiah Ekonomi Islam, 2024)
The human aspect is essential in achieving organizational goals because satisfied employees will perform harder and more productively, allowing companies to gain a competitive advantage. This research aims to identify the elements that influence employee work satisfaction at Bank Syariah Indonesia in Ternate. Employees of Bank Syariah Indonesia in Ternate were the subject of the study. This is a quantitative analysis of the total population of all Bank Syariah Indonesia employees in Ternate. According to the study's findings, leadership has a favorable impact on employee work satisfaction. Islamic work principles improve Employee Job satisfaction. Employee compensation moderates leadership and has little effect on employee work satisfaction. Employee Job satisfaction is influenced by Islamic work principles, moderated by employee compensation. Work ethics in Islam have an excellent impact on religion. Employee Job satisfaction is positively influenced by religion. Islamic work principles, as mediated through religion, impact employee job satisfaction.